Quantitative analysis of iridocorneal angle and ciliary cleft structures in canine eyes using ultrasound biomicroscopy - Kim, Donghee; Kwon, Hyun; Hwang, Jiyi; Jung, Ji Seung; Park, Kyung-Mee (Frontiers in Veterinary Science, 2024)
IntroductionThis study aimed to examine the relationship between the relative opening of the ICA (RO-ICA) and the structure of the ciliary cleft (CC) using Ultrasound Biomicroscopy (UBM).Materials and methodsClinical data from 31 eyes of 17 dogs at the Veterinary Teaching Hospital of Chungbuk National University, Korea, were analyzed. RO-ICA was categorized as “Slightly Narrow”, “Narrow”, “Open”, and “Wide Open”, with eyes further grouped into “Narrow” (including Slightly Narrow and Narrow) and “Open” (including Open and Wide Open) for analysis. Statistical methods, including linear regression and average comparisons between groups, were employed to explore correlations between RO-ICA and parameters such as ICA, CC width (CCW), CC length (CCL), and CC area (CCA).ResultsThe distribution showed “Narrow” (3 eyes, 9.7%), “Slightly Narrow” (13 eyes, 41.9%), and “Open” (14 eyes, 45.2%) as the predominant categories. In the Open group, CCL and CCA were significantly larger compared to the Narrow group. A positive correlation was observed between RO-ICA and CCL, and CCA across all groups. Notably, in the Narrow group, RO-ICA demonstrated a particularly significant positive correlation with all assessed parameters, including ICA, CCW, CCL, and CCA. However, no significant correlation was observed between RO-ICA and the assessed parameters in the Open group. In conclusion, while a smaller RO-ICA generally correlates with a smaller CC, a larger RO-ICA does not guarantee a larger CC.ConclusionAdditional UBM examinations are recommended for comprehensive evaluations, particularly in cases where gonioscopy indicates an open iridocorneal angle.